Utilizing learning communities to deliver an integrated undergraduate medical education curriculum. Issue 1 (1st January 2022) - Braunreiter, Chi; Sudhanthar, Sathyanarayan; Riley, Brad; Armstrong, Kelly; Mavis, Brian; Gold, Jonathan
ABSTRACT: Aim: Learning communities (LCs) have been identified as a structure to support student wellness as well as create a positive learning environment and have been increasingly adopted in undergraduate medical education (UGME). In 2016, Michigan State University College of Human Medicine made curricular changes which integrated basic, social, and clinical sciences. One of the major strategies adopted to deliver this integrated curriculum was to create LCs that served as a central scaffold for students' academic development. Our primary aim is to describe how the school utilized LC faculty to deliver this core integrated curriculum. Methods: Students were surveyed about their perceptions of the effectiveness of the LCs in delivering an integrated science curriculum. Student academic performance in the new curriculum was compared to that of students from the legacy curriculum as a measure of the effectiveness of the curricular changes. Results: The percentage of students in each class who responded to surveys ranged between 78.7% and 95.8%. Mean Likert responses (1 = strongly disagree; 5 = strongly agree) for statements 'the Faculty Fellow is effective in helping me learn the scholar group content', 'the Faculty Fellow is an effective teacher in our scholar group', and 'the Faculty Fellow is well prepared for our scholar group' ranged from 4.37 to 4.78, 4.72 to 4.76, and 4.81 to 4.86, respectively. In addition, a comparison of summative exam scores of the new curriculum's students to the legacy curriculum's students demonstrated comparable or better performances in the new curriculum. Conclusions: Utilizing LCs to deliver an integrated science curriculum is an underutilized strategy in UGME. Surveys on student satisfaction and academic performance are encouraging. Additional outcome measures are planned to continually evaluate this innovative multifaceted integration.